2020
DOI: 10.1038/s41419-020-03059-8
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte apoptosis: the roles and key molecular mechanisms in resorption-related bone diseases

Abstract: Vital osteocytes have been well known to function as an important orchestrator in the preservation of robustness and fidelity of the bone remodeling process. Nevertheless, some key pathological factors, such as sex steroid deficiency and excess glucocorticoids, and so on, are implicated in inducing a bulk of apoptotic osteocytes, subsequently resulting in resorption-related bone loss. As much, osteocyte apoptosis, under homeostatic conditions, is in an optimal state of balance tightly controlled by pro- and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 176 publications
(437 reference statements)
2
69
0
2
Order By: Relevance
“…Thus, it was concluded that, in the process of cancer progression, the analysis of ROS level fluctuation may be of importance for cancer prevention and treatment. Furthermore, autophagy is triggered in response to all types of biological stress, including increased oxidative stress ( 40 ). The fluorescence microscopy results of the present study revealed that NAC pretreatment may act as an antioxidant which remarkably inhibits ROS production and the transition from LC3I to LC3II in treated cells, thus suggesting that NAC exhibited a considerable blocking effect on chrysin-induced autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was concluded that, in the process of cancer progression, the analysis of ROS level fluctuation may be of importance for cancer prevention and treatment. Furthermore, autophagy is triggered in response to all types of biological stress, including increased oxidative stress ( 40 ). The fluorescence microscopy results of the present study revealed that NAC pretreatment may act as an antioxidant which remarkably inhibits ROS production and the transition from LC3I to LC3II in treated cells, thus suggesting that NAC exhibited a considerable blocking effect on chrysin-induced autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of isolated osteoblast death during homeostasis and medical treatment, as well as their replacement, are not particularly clear. In recent years, osteocytes have gained center stage as sensors of biomechanical strain and players in modeling and remodeling of bone (BONEWALD, 2007;Kennedy et al, 2012;Ru & Wang, 2020). However, osteoblasts, mirroring the pre-osteocytic cell stage, have suggested to play a similar role in sensation of microscopic tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…показали в исследованиях на крысах, что лечение антителами к склеростину ускоряет образование кости и костной массы, а также положительно влияет на увеличение ее прочности [34]. Кроме того, есть мнение, что кость, образовавшаяся при блокировании склеростина, впоследствии не истощается в результате снижения функциональной активности, по крайней мере, на ранней стадии [35]. Таким образом, позитивные результаты изучения механизма действия склеростина и его подавления различными препаратами могут быть применены в реальной клинической практике для достижения ускоренной консолидации перелома.…”
Section: моноклональное антитело к склеростинуunclassified